2007
DOI: 10.2141/jpsa.44.339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oxidative Stress and its Amelioration through Certain Antioxidants in Broilers during Summer

Abstract: A comparative study on antioxidative e#ects of vitamin E, amla-electrolyte (Electrolyte mix of Emblica o$cinalis) and mint (Mentha longifolia) supplementation in broilers was conducted during the summer months of May-July with temperature-humidity index ranging from 1-to 2*. Day old broiler chicks (nῌ1/) were randomly divided into five groups. Control group was given basal diet and treatment groups were supplemented with either Vitamin E (,** mg/kg feed), dried mint leaves (+* g/kg and -* g/kg feed) or amla-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
4
30
2
1
Order By: Relevance
“…The elevation of tissue lipid peroxidation leads to free radical buildup and, when the anti-oxidative capacity of the organism is overcome, there is a decrease in growth performance, and carcass quality traits may be affected. The high content of polyunsaturated fatty acids in chicken meat contributes to this quality decline (Lanari et al, 2004;Maini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of tissue lipid peroxidation leads to free radical buildup and, when the anti-oxidative capacity of the organism is overcome, there is a decrease in growth performance, and carcass quality traits may be affected. The high content of polyunsaturated fatty acids in chicken meat contributes to this quality decline (Lanari et al, 2004;Maini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, other authors observed an improvement in the performance variables when they included selenium or vitamin E in broiler diets. Maini et al (2007) observed an improvement of approximately Means followed by the same letter in columns do not differ by the SNK test (P> 0.05). *Differs from the control treatment by Dunnett's test (P <0.05).…”
Section: Resultsmentioning
confidence: 83%
“…When the stress is prolonged or very aggressive, the body's antioxidant capacity is exceeded, which impairs cellular functions and consequently leads to a decrease in production performance (Maini et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…High environmental temperatures stimulate the hypothalamo hypophysealadrenocortical axis which increases corticosteroid secretion in response to stress (Maini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%